Method for producing hairspring for timepiece movement

By using niobium and hafnium alloy blanks, annealing, depositing ductile material layers and multiple deformation treatments in the watch hairspring manufacturing process, the problems of adhesion and biting during the hairspring manufacturing process in the prior art are solved, and high yield strength is achieved and low thermal elasticity coefficient of hairspring manufacturing.

CN119472216APending Publication Date: 2025-02-18NIVAROX FAR SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411661811.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-05-07
Filing Date
2020-05-06
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing watch hairsprings have problems with adhesion and bite during the manufacturing process, and it is difficult to convert into filaments by standard methods, especially in drawing and rolling operations.

Method used

A manufacturing method is adopted, including manufacturing a blank made of niobium and hafnium alloys, annealing and cooling, depositing a layer of ductile material, undergoing multiple deformations and heat treatments, and ultimately forming a hairspring with high yield strength and low thermal elasticity coefficient.

Benefits of technology

This method effectively promotes the forming and deformation of NbHf alloy billets, especially in drawing, wire drawing and rolling operations, improving the mechanical properties and manufacturing ease of the hairspring.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a hairspring to be mounted on a balance of a timepiece movement, comprising:-a step of manufacturing a blank made of a niobium and hafnium alloy containing 5 to 60 wt.%, preferably 5 to 30 wt.%, more preferably 8 to 12 wt.% hafnium,-a step of annealing and cooling said blank,-at least one step of deforming the annealed blank to form a wire,-a step of cooling the wire,-a step of forming the wire,-a step of forming the wire,-a step of forming the wire,-a step of forming the wire, and-a step of forming the wire. Characterized in that it comprises, prior to the deforming step, a step of depositing on the blank a layer of a ductile material selected from the group consisting of copper, nickel, copper-nickel alloy, copper-manganese alloy, gold, silver, nickel-phosphorus (Ni-P) and nickel-boron (Ni-B) in order to facilitate the wire forming operation. The invention further relates to a hairspring produced by said production method.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with application number 202010372078.1, application date May 6, 2020, and invention name “Method for manufacturing a hairspring for a watch movement”. Technical Field

[0002] The present invention relates to a method for manufacturing a hairspring to be assembled on a balance wheel of a timepiece movement. It also relates to a hairspring made of a Nb-Hf alloy using this method. Background Art

[0003] The manufacture of balance springs for watches is subject to constraints that often seem incompatible at first glance:

[0004] -High yield strength is required,

[0005] -Ease of manufacturing, especially wire drawing and rolling operations,

[0006] -Excellent fatigue strength,

[0007] - stability of performance levels over time,

[0008] - Small cross section.

[0009] The manufacture of the hairspring also focuses on temperature compensation to ensure a consistent level of chronometric performance. This requires obtaining a thermoelastic coefficient close to 0. Hairsprings with limited sensitivity to magnetic fields are also sought.

[0010] Balance springs have been developed using niobium and hafnium alloys. However, these alloys cause problems involving sticking and galling in the drawing or drawing templates (diamond or hard metal) and on the rollers (hard metal or steel), making it almost impossible to convert them into fine wires using standard methods such as for steel.

[0011] Any improvement in at least one of these points, particularly ease of manufacture, and in particular ease of wire drawing and rolling operations, therefore represents a significant advance. Summary of the invention

[0012] One object of the present invention is to propose a method for manufacturing a balance spring to be fitted to a balance of a timepiece movement which facilitates the deformation and more particularly the rolling operation.

[0013] To this end, the invention relates to a method for manufacturing a balance spring to be fitted to a balance wheel of a timepiece movement, comprising:

[0014] - a step of manufacturing a billet made of a niobium and hafnium alloy, said alloy containing:

[0015] -Niobium: up to 100% by weight

[0016] - hafnium: between 5 and 60% by weight, preferably between 5 and 30% by weight, more preferably between 8 and 12% by weight,

[0017] - one or more elements selected from Ti, Zr, Ta and W, the percentage of each element being in the range of 0 to 2 wt. %, preferably in the range of 0.2 to 1.5 wt. %,

[0018] - impurities, the total percentage of which is in the range of 0 to 0.5 wt. %. More specifically, the impurities may be trace elements selected from O, H, C, Fe, N, Ni, Si, Cu, Al, Cr, Mn, V, Sn, Mg, Mo, Pb, Co and B, each of which is present in an amount of 0 to 1,000 wt. ppm,

[0019] - a step of annealing and cooling the billet, followed by a step of deforming the annealed billet to form a wire, said annealing and deformation steps being repeated several times,

[0020] - a winding step for forming a balance spring,

[0021] - Final heat treatment step.

[0022] According to the invention, the method comprises, before the deformation step and after the annealing step, a step of depositing on said billet a layer of ductile material selected from copper, nickel, copper-nickel alloys, copper-manganese alloys, gold, silver, nickel-phosphorus Ni-P and nickel-boron Ni-B to facilitate the wire forming operation. The thickness of the deposited layer of ductile material is preferably selected so that, for a given wire cross-sectional area, the ratio of the ductile material area to the NbHf alloy area is less than 1, preferably less than 0.5, more preferably between 0.01 and 0.4.

[0023] Such a manufacturing method facilitates the shaping of the NbHf alloy billet into a wire, and more particularly facilitates the drawing, wire drawing and rolling operations. In particular, this method is advantageous for manufacturing a balance spring having the following composition:

[0024] -Niobium: up to 100% by weight

[0025] - hafnium: between 5 and 15% by weight, preferably between 8 and 12% by weight,

[0026] - one or more elements selected from Ti, Zr, Ta and W, the percentage of each element being in the range of 0.2 to 1.5 wt. %,

[0027] - Impurities, the total percentage of which is in the range from 0 to 0.5% by weight. DETAILED DESCRIPTION

[0028] The invention relates to a method for manufacturing a balance spring to be fitted to a balance wheel of a timepiece movement and made of an alloy containing niobium and hafnium.

[0029] The method comprises the following steps:

[0030] - a step of manufacturing a billet made of a niobium and hafnium alloy, said alloy containing:

[0031] -Niobium: up to 100% by weight

[0032] - hafnium: between 5 and 60% by weight, preferably between 5 and 30% by weight, more preferably between 8 and 12% by weight,

[0033] - one or more elements selected from Ti, Zr, Ta and W, the percentage of each element being in the range of 0 to 2 wt. %, preferably in the range of 0.2 to 1.5 wt. %,

[0034] - impurities, the total percentage of which is in the range of 0 to 0.5 wt. %. More specifically, the impurities may be trace elements selected from O, H, C, Fe, N, Ni, Si, Cu, Al, Cr, Mn, V, Sn, Mg, Mo, Pb, Co and B, each of which is present in an amount of 0 to 1,000 wt. ppm,

[0035] - a step of annealing the billet followed by cooling the billet,

[0036] - a step of depositing ductile material on said blank,

[0037] - at least one step of deforming the blank to form a wire, with annealing and cooling steps between the deformation steps in the case of a plurality of deformation steps,

[0038] - a winding step for forming a balance spring,

[0039] - A final heat treatment step to fix the shape of the balance spring and adjust the thermoelastic coefficient.

[0040] In a particularly preferred manner, the blank contains 8 to 12 wt. % hafnium, Ti, Zr, Ta and W, the percentage of each element being in the range of 0.2 to 1.5 wt. %, more preferably Ti in the range of 0.5 to 1.5 wt. %, Zr in the range of 0.5 to 0.9 wt. %, Ta in the range of 0.3 to 0.7 wt. % and W in the range of 0.3 to 0.7 wt. %.

[0041] Preferably, the NbHf alloy billet used in the present invention does not contain any other elements except any potential and unavoidable trace elements. This can prevent the formation of brittle phases.

[0042] More particularly, the oxygen content is less than or equal to 0.10% by weight of the total composition, in particular less than or equal to 0.05% by weight of the total composition, or even less than or equal to 0.03% by weight of the total composition.

[0043] More particularly, the carbon content is less than or equal to 0.04% by weight of the total composition, in particular less than or equal to 0.02% by weight of the total composition, or even less than or equal to 0.015% by weight of the total composition.

[0044] More particularly, the iron content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.02% by weight of the total composition, or even less than or equal to 0.005% by weight of the total composition.

[0045] More particularly, the nitrogen content is less than or equal to 0.04% by weight of the total composition, in particular less than or equal to 0.02% by weight of the total composition, or even less than or equal to 0.015% by weight of the total composition.

[0046] More particularly, the hydrogen content is less than or equal to 0.01% by weight of the total composition, in particular less than or equal to 0.0035% by weight of the total composition, or even less than or equal to 0.001% by weight of the total composition.

[0047] More particularly, the silicon content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.02% by weight of the total composition, or even less than or equal to 0.005% by weight of the total composition.

[0048] More particularly, the nickel content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0049] More particularly, the content of elements in ductile solid solution, such as copper, in the alloy is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.004% by weight of the total composition.

[0050] More particularly, the aluminum content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0051] More particularly, the chromium content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0052] More particularly, the manganese content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0053] More particularly, the vanadium content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0054] More particularly, the tin content is less than or equal to 0.01% by weight of the total composition, in particular less than or equal to 0.0035% by weight of the total composition, or even less than or equal to 0.001% by weight of the total composition.

[0055] More particularly, the magnesium content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0056] More particularly, the molybdenum content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0057] More particularly, the lead content is less than or equal to 0.05% by weight of the total composition, in particular less than or equal to 0.01% by weight of the total composition, or even less than or equal to 0.002% by weight of the total composition.

[0058] More particularly, the cobalt content is less than or equal to 0.01% by weight of the total composition, in particular less than or equal to 0.0035% by weight of the total composition, or even less than or equal to 0.001% by weight of the total composition.

[0059] More particularly, the boron content is less than or equal to 0.005% by weight of the total composition, in particular less than or equal to 0.0001% by weight of the total composition.

[0060] The annealing step is a solution treatment in vacuum at a temperature of 650°C to 1,750°C for preferably 5 minutes to 2 hours, followed by quenching in gas, for example, to obtain a supersaturated solid solution of Hf in β-phase Nb. According to another embodiment, natural cooling in vacuum is also conceivable.

[0061] More particularly, the deposition step for forming the object of the invention consists of depositing a layer of ductile material selected from copper, nickel, copper-nickel alloys, copper-manganese alloys, gold, silver, nickel-phosphorus Ni-P and nickel-boron Ni-B to facilitate the wire forming operation. Preferably, the thickness of the deposited ductile material layer is selected so that the ratio of the ductile material area to the NbHf alloy area at a given wire cross-sectional area is less than 1, preferably less than 0.5, more preferably in the range of 0.01 to 0.4. For example, for a total wire diameter of 0.1 mm, the ductile material layer may have a thickness of 7 μm at a cross-sectional area of ​​the NbHf alloy of 0.086 mm in diameter. This corresponds to a copper area of ​​0.35 (0.002 mm 2 ) and NbHf area (0.0058mm 2 ) ratio.

[0062] This thickness of ductile material, particularly copper, makes it easy to draw, wire draw and roll the composite Cu / NbHf material. More specifically, the copper thickness is optimized so that the tip created by filing or hot drawing required to insert the wire into the drawing plate during the drawing or wire drawing operation is coated with copper.

[0063] Ductile material, preferably copper, is therefore deposited at a given moment to facilitate the wire forming operations by drawing, wire drawing and rolling, retaining a thickness of preferably 1 to 500 microns on a wire having an overall diameter of 0.2 to 1 mm.

[0064] The addition of ductile material can be electroplated, by PVD or CVD or mechanical; in this case it is a sleeve or tube of ductile material such as copper conditioned on a large diameter NbHf alloy rod, which is then tapered during one or more deformation steps of the composite rod. Thus, one possibility involves forming a composite billet by assembling the Nb-Hf rod and the copper sleeve, which is then extruded.

[0065] The deformation step refers in general to one or more deformation treatments, which may include wire drawing and / or rolling. Wire drawing requires the use of one or more drawing plates in the same deformation step or in different deformation steps, if necessary. Wire drawing is performed until a wire with a circular cross section is obtained. Rolling may be performed during the same deformation step as wire drawing or in another subsequent deformation step. Advantageously, the final deformation treatment applied to the alloy is a rolling operation, preferably with a rectangular profile compatible with the inlet cross section of a winder spindle.

[0066] The method may include one or more deformation steps, each step having a deformation ratio in the range of 1 to 5, preferably in the range of 2 to 5, the deformation ratio satisfying the general formula 2ln(d0 / d), where d0 and d are the diameters before and after deformation, respectively. The total deformation ratio may be in the range of 1 to 14.

[0067] The method may comprise intermediate annealing steps between the different deformation steps.

[0068] The method of the invention preferably comprises, after the deformation step, a step of removing said layer of ductile material. Preferably, the ductile material is removed once all deformation operations have been carried out, i.e. after the final rolling operation and before the coiling operation. However, this does not exclude the removal of the layer of ductile material before all deformation operations have been completed. Thus, when rolling in multiple stages, the layer of ductile material may be removed before the final rolling stage. Preferably, the layer of ductile material, such as copper, is removed from the wire, in particular by etching with a cyanide-based or acid-based solution, such as nitric acid.

[0069] Except for the intermediate annealing operation performed between the deformation steps, the annealing before the deformation step is performed at a temperature of 650° C. to 1,750° C. for a duration of 5 minutes to 2 hours, preferably 10 minutes to 1 hour.

[0070] The final heat treatment after coiling is carried out at a temperature of 500 to 1,250° C. for a duration of 30 minutes to 30 hours. Depending on the composition and temperature of the alloy, a body-centered cubic single-phase structure or a two-phase structure having a body-centered cubic structure and a hexagonal close-packed structure can be obtained at the end of this heat treatment.

[0071] The method of the invention makes it possible to manufacture, and more particularly to shape, a balance spring made of an alloy of the niobium-hafnium type. This alloy has high mechanical properties, combining a very high yield strength, greater than 600 MPa, with a very low elastic modulus, of the order of 60 GPa to 100 GPa. This combination of properties is very suitable for a balance spring. Moreover, this alloy is paramagnetic.

[0072] Binary alloys containing niobium and hafnium of the type described above and used in the implementation of the invention also have an effect similar to that of "Elinvar", having a thermoelastic coefficient of almost zero within the normal operating temperature range of a watch and are suitable for making self-compensating balance springs.

Claims

1. A hairspring to be fitted to a balance wheel of a watch movement, said hairspring being made of a niobium-hafnium alloy containing: -Niobium: up to 100% by weight -Hafnium: between 5 and 15% by weight, - one or more elements selected from Ti, Zr, Ta and W, the percentage of each element being in the range of 0.2 to 1.5 wt. %, - impurities, the total percentage of which is in the range of 0 to 0.5% by weight, The niobium-hafnium alloy has a yield strength higher than 600 MPa and an elastic modulus of 60 GPa to 100 GPa.

2. A balance spring according to claim 1, characterized in that The alloy contains between 8 and 12 weight percent hafnium.

3. A balance spring according to claim 1 or 2, characterized in that It contains Ti, Zr, Ta and W, and the weight percentage of each element is in the range of 0.2 to 1.5 weight %.

4. A balance spring according to claim 3, characterized in that The weight percentage of Ti is in the range of 0.5 to 1.5 weight %, the weight percentage of Zr is in the range of 0.5 to 0.9 weight %, the weight percentage of Ta is in the range of 0.3 to 0.7 weight %, and the weight percentage of W is in the range of 0.3 to 0.7 weight %.